Somatic/Germinal Mosaicism of a F8 Promoter Deletion Confounds Clinical Predictions in a Family with Haemophilia A: Key Role of Genotype Quantitation - Abelleyro, Miguel Martin (2018)
Large F8 deletions cause 10-15% of severe-Haemophilia A (HA) cases and associate with the highest clinical/biochemical severity and with significantly augmented risks for developing inhibitors against therapeutic FVIII. Only 45-50% of severe-HA cases present family history of the disease. In the remnant cases (sporadic-HA), the mutation origin defines different clinical scenarios in which the risk of recurrence and thus genetic counselling significantly vary. The origin of the causative mutation may be either pre-zygotic or post-zygotic generating a genetic mosaicism affecting, partially or totally, one or more tissue/organs including the gonads. Furthermore, the technical features of the genotyping approach for detecting and measuring an eventual genetic mosaicism critically affect its diagnosis. The quali-quantitative extent of somatic and germinal mosaicisms is passively assumed to be associated with the phenotypic expression of haemophilia severity and inheritance pattern, respectively. We present a case of a family affected with HA in which the clinical/biochemical severity and inheritance patterns associate with the observed fraction of mosaic cells bearing a F8-promoter deletion.